2022
DOI: 10.1021/acs.orglett.2c00084
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Ring Opening of Arylcyclopropanecarboxamides Accompanied by Borylation and Enolate Formation

Abstract: Treatment of arylcyclopropanecarboxamides with a sodium dispersion in the presence of methoxypinacolborane as a reduction-resistant electrophile leads to reductive cleavage of the cyclopropane ring followed by instant trapping with the boron electrophile to yield the enolates of γ-aryl-γ-borylalkanamides. The enolates react further with a different electrophile to yield the corresponding α-substituted amides with anti selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Our group has recently reported that the Au/TiO 2 -catalyzed silaboration of aryl-substituted cyclopropyl aldehydes gives acyclic β-boronate silyl enol ethers via ring-opening of the cyclopropane ring (Scheme ). A very similar ring-opening borylation concept with methoxypinacolborane has been reported more recently in the case of aryl cyclopropane carboxamides using Na metal as a one-electron donor . Given the facile activation of hydrosilanes on Au nanoparticles, which enables their addition on a variety of functional groups, in this manuscript, we report our studies regarding the reaction between cyclopropyl aldehydes or ketones with hydrosilanes using supported Au nanoparticles on titania (Au/TiO 2 ) as the catalyst.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our group has recently reported that the Au/TiO 2 -catalyzed silaboration of aryl-substituted cyclopropyl aldehydes gives acyclic β-boronate silyl enol ethers via ring-opening of the cyclopropane ring (Scheme ). A very similar ring-opening borylation concept with methoxypinacolborane has been reported more recently in the case of aryl cyclopropane carboxamides using Na metal as a one-electron donor . Given the facile activation of hydrosilanes on Au nanoparticles, which enables their addition on a variety of functional groups, in this manuscript, we report our studies regarding the reaction between cyclopropyl aldehydes or ketones with hydrosilanes using supported Au nanoparticles on titania (Au/TiO 2 ) as the catalyst.…”
Section: Introductionmentioning
confidence: 72%
“…14 A very similar ring-opening borylation concept with methoxypinacolborane has been reported more recently in the case of aryl cyclopropane carboxamides using Na metal as a one-electron donor. 15 Given the facile activation of hydrosilanes on Au nanoparticles, which enables their addition on a variety of functional groups, 16 in this manuscript, we report our studies regarding the reaction between cyclopropyl aldehydes or ketones with hydrosilanes using supported Au nanoparticles on titania (Au/TiO 2 ) as the catalyst. The question regarding this reaction is whether cyclopropyl C−C cleavage could be achieved or it would simply lead to the reduction of the carbonyl group.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When sodium dispersion was placed from the beginning, the yield of 2a was 47%, and 29% of 1a was recovered (entry 13), which resulted from the over-reduction of 2a and the resulting shortage of sodium dispersion as well as changes in particle size upon adding sodium dispersion in THF. 7f When sodium dispersion was added in 1 s, the yield of 2a was 52%, and 26% of 1a was recovered (entry 14) probably because of similar reasons. Too slow addition, over 5 min, also resulted in a lower yield and recovery of 1a (12%) (entry 15) although the reason is unclear.…”
Section: Table 1 Screening Of Conditions For Reductive ...mentioning
confidence: 97%